Magic of the lost story - Murty, Sudha; Yambem, David (India : Puffin Books, 2022)
"After staying in the lockdown for over a year, Nooni is now visiting her Ajja-Ajji in Somanahalli. Memories of excavating the famous stepwell and experiencing village life for the first time in The Magic of the Lost Temple are still afresh in Nooni's mind. Excited to finally step out of the confines of her home, little does Nooni know she will make yet another discovery, only this time it's a missing puzzle in her family's history. Written in India's favourite storyteller's inimitable style, The Magic of the Lost Story captures the value of asking questions and keeping the answers alive. Packed with delightful artworks and wondrous terrains, this story takes you on an unforgettable journey as it follows the magnificent Tungabhadra River." --publisher's website.
"Sequel to the bestselling novel, The Magic of the lost temple"--Cover.
Ages 8 and up.
Keywords: Girls -- India -- Juvenile fiction; Children's stories, Indic (English); Tungabhadra River (India) -- Juvenile fiction